Access to Education and Income Inequality Nexus: Findings from a Cross-sectional Survey (Global Journal of Human-Social Science, 2021)
The study examines how unequal access to education affects individuals future income generation An individual s access to education has been defined by certain key variables family size the distance of the school from home location of the school level of education of parents availability of financial aid expenditure on education quota facility etc The study is cross-sectional in nature drawing data from employees of all levels working at the Bangladesh University of Professionals The paper reveals that an individual s level of education parents education level expenditure on education financial aid and quota facility have a significant positive effect on income generation in the future On the contrary family size both location and distance of the school have a negative impact on income generation It is shown that access to education is hindered for individuals completing schools at sub-urban or rural locations than those from urban regions which culminate into the lower-income generation in the future